Effectiveness of Financial Performance and Capital Structure on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Mita Wulandari; Hasbiana Dalimunthe; Retnawati Siregar (Universitas Medan Area, 2022)
This study aims to determine the effect of financial performance and capital structure on the value of the company. This study uses secondary data in the form of company financial statements. Sampling using purposive sampling technique. Data analysis using classical assumption tests and multiple linear regression. The population of this study is food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2019 period with a total sample of 15 companies. The results of testing the first hypothesis show that Financial Performance has a significant positive effect. The results of testing the second hypothesis show that the Capital Structure has a significant positive effect. The results of the third hypothesis test show that Financial performance (X1) and Capital Structure (X2) have a Simultaneous effect on Company Value (Y). Advice for investors to pay attention to the profitability and capital structure generated by the company in order to obtain higher returns